Behind sleepy eyes: Implications of sleep loss for organizations and employees - Budnick, Christopher J.; Barber, Larissa K. (Translational Issues in Psychological Science, 2015)
Sleep loss and daytime sleepiness are common experiences for employees across many occupations. Although researchers commonly focus on the detrimental effects of sleep issues for attention and vigilance during task performance, we review research that examines how sleep issues influence interpretations of, and interactions in, the work environment. This review begins by differentiating between sleep loss and sleepiness. We then highlight how sleep issues can negatively bias the interpretation of environmental information and result in aggressive responding. We also examine how sleep issues impair self-regulatory ability and contribute to workplace deviance. After each section, we discuss the implications of these findings for the work environment. A closer examination of sleep’s influence on workplace interactions can spur a beneficial discussion for researchers across a variety of disciplines and employees across all organizational levels. (PsycInfo Database Record (c) 2022 APA, all rights reserved)
Keywords: Aggressive Behavior; Employee Productivity; Health; Occupations; Organizations; Personnel; Self-Control; Sleep Deprivation; Sleepiness; Stress; Working Conditions; dept.psy

Turning molehills into mountains: Sleepiness increases workplace interpretive bias - Barber, Larissa K.; Budnick, Christopher J. (Journal of Organizational Behavior, 2015)
Three studies draw from evolutionary theory to assess whether sleepiness increases interpretive biases in workplace social judgments. Study 1 established a relationship between sleepiness and interpretive bias using ambiguous interpersonal scenarios from a measure commonly used in personnel selection (N = 148). Study 2 explored the boundary conditions of the sleepiness–interpretive bias link via an experimental online field survey of U.S. adults (N = 433). Sleepiness increased interpretive bias when social threats were clearly present (unfair workplace) but did not affect bias in the absence of threat (fair workplace). Study 3 replicated and extended findings from the previous two studies using objective measures of sleep loss and a quasi-experimental manipulation of minor sleep loss (N = 175). Negative affect, ego depletion, or personality variables did not influence the observed relationships. Overall, results suggest that a self-protection/evolutionary perspective best explains the effects of sleepiness on workplace interpretive biases. These studies advance the current research on sleep in organizations by adding a cognitive “threat interpretation” bias approach to past work examining the emotional reaction/behavioral side of sleep disruption. Interpretive biases due to sleepiness may have significant implications for employee health and counterproductive behavior. Copyright © 2015 John Wiley & Sons, Ltd.
Keywords: Conditional Reasoning Test of Aggression; dept.psy; fairness; interpretive bias; sleep; work perceptions

The fear of missing out at work: Examining costs and benefits to employee health and motivation - Budnick, Christopher J.; Rogers, Arielle P.; Barber, Larissa K. (Computers in Human Behavior, 2020)
The popular business media argues that the “fear of missing out” (FoMO) on work-related opportunities harms employees’ health and performance. Yet, these claims rely on the study of FoMO in college students in non-work contexts. Therefore, we explored workplace FoMO among employees across three studies. We first developed a measure and provided validation evidence for workplace FoMO among diverse employees (N = 324; Study 1) and MBA students (N = 223; Study 2). Using a third large employee sample (N = 300; Study 3), we tested whether workplace FoMO predicted health (i.e., work burnout and work well-being) and motivational outcomes (i.e., message-checking behaviors and work engagement). We also examined whether family-supportive organizational perceptions (FSOP) moderated these relationships. Results indicated that workplace FoMO is a distinct construct from other measures, including general FoMO. Workplace FoMO also predicted work burnout and message checking behavior, but not work well-being. Lower levels of FSOP strengthened the positive relationship between workplace FoMO and message checking behavior, but also produced a positive relationship between workplace FoMO and work well-being. Overall, FoMO appears to be relevant to the work context and predicts both employee well-being and behavior outcomes. © 2019 Elsevier Ltd
Keywords: Behavioral research; College students; Costs and benefits; Employee health; Fear of missing out; Health; Job satisfaction; Motivation; Students; Technology use; Technology use at work; Well being; Work engagements; Work-related; article; burnout; controlled study; dept.psy; fear of missing out; human; major clinical study; motivation; peer-reviewed; perception; wellbeing; work engagement

College student sleep and executive functioning: An examination of potential moderators - Cifre, Anthony B.; Walters, Kenneth S.; Budnick, Christopher J. (Translational Issues in Psychological Science, 2020)
Approximately 60% of college students report sleep disturbances. Sleep disturbances, such as insomnia, negatively influence physical energy, cognitive resources, and affective states that might inhibit executive functioning. To better delineate the variables that alter the college student insomnia and executive functioning relationship we examined sleepiness, sleep debt, and attention-deficit/hyperactivity disorder (ADHD) symptomatology. We expected insomnia to predict executive dysfunction, with a stronger relationship observed at higher levels of the focal moderator (i.e., sleepiness, sleep debt, or ADHD symptoms). Undergraduate participants (n = 472) completed a cross-sectional survey assessing insomnia, state sleepiness, sleep debt, ADHD symptomatology (inattention, hyperactivity, and impulsivity), and executive dysfunction. Hierarchical linear regressions showed that poor sleep had a negative influence on executive function when college students also had high levels of impulsivity, state sleepiness, or sleep debt. These results partially support our expectations and further the academic sleep-related literature while providing insight for counselors, academic advisors, or other professionals working with college student populations. (PsycInfo Database Record (c) 2020 APA, all rights reserved)
Keywords: Attention Deficit Disorder with Hyperactivity; College Students; Executive Function; Financial Strain; Insomnia; Sleep; Sleepiness; Symptoms; dept.psy; peer-reviewed

Writing Wisdom, Reviewing Identity: Positive Outcomes of Participating in a Memoir Course for Older Adults - Bivona, Marissa A.; Kahlbaugh, Patricia E.; Budnick, Christopher J. (The International Journal of Reminiscence and Life Review, 2020)
Constructing a personal narrative and consolidating identity is an ongoing process that becomes pressing in the face of mortality. The current pilot study examined the process of life review in a sample of older people, specifically examining the effects of participation in a memoir course on wisdom, identity, and well-being. We hypothesized that wisdom, identity fidelity and coherence, and subjective well-being would increase for those in the memoir group compared to a control. Eighteen elderly individuals from two senior retirement communities were randomly assigned to participate in weekly classes, for four weeks, either to work on a memoir or discuss films (control group). After engaging in the process of organizing their life story and writing about important memories, the nine individuals in the memoir group scored significantly higher on self-report measures of wise reminiscence, identity fidelity, and subjective well-being compared to those in the control group. Furthermore, exploratory analyses found that wise reminiscence statistically mediated relationships between the memoir condition and the outcome measures of identity fidelity, identity coherence, and subjective well-being. These findings point to the benefits of memoir writing for positive aging as well as potential mechanisms underlying its effectiveness.
Keywords: Identity; Life Review; Narrative; Subjective Well-Being; Wisdom; dept.psy

College student Fear of Missing Out (FoMO) and maladaptive behavior: Traditional statistical modeling and predictive analysis using machine learning - McKee, Paul C.; Budnick, Christopher J.; Walters, Kenneth S.; Antonios, Imad (PLOS ONE, 2022)
This paper reports a two-part study examining the relationship between fear of missing out (FoMO) and maladaptive behaviors in college students. This project used a cross-sectional study to examine whether college student FoMO predicts maladaptive behaviors across a range of domains (e.g., alcohol and drug use, academic misconduct, illegal behavior). Participants (N = 472) completed hard copy questionnaire packets assessing trait FoMO levels and questions pertaining to unethical and illegal behavior while in college. Part 1 utilized traditional statistical analyses (i.e., hierarchical regression modeling) to identify any relationships between FoMO, demographic variables (socioeconomic status, living situation, and gender) and the behavioral outcomes of interest. Part 2 looked to quantify the predictive power of FoMO, and demographic variables used in Part 1 through the convergent approach of supervised machine learning. Results from Part 1 indicate that college student FoMO is indeed related to many diverse maladaptive behaviors spanning the legal and illegal spectrum. Part 2, using various techniques such as recursive feature elimination (RFE) and principal component analysis (PCA) and models such as logistic regression, random forest, and Support Vector Machine (SVM), showcased the predictive power of implementing machine learning. Class membership for these behaviors (offender vs. non-offender) was predicted at rates well above baseline (e.g., 50% at baseline vs 87% accuracy for academic misconduct with just three input variables). This study demonstrated FoMO’s relationships with these behaviors as well as how machine learning can provide additional predictive insights that would not be possible through inferential statistical modeling approaches typically employed in psychology, and more broadly, the social sciences. Research in the social sciences stands to gain from regularly utilizing the more traditional statistical approaches in tandem with machine learning.
Keywords: Alcohol consumption; Behavior; Cannabis; Drug interactions; Forecasting; Machine learning; Machine learning algorithms; Principal component analysis; dept.csc; dept.psy; peer-reviewed

The role of combat exposure on drinking behavior and subjective well-being: A Rubin Causal Model approach. - McKee, Paul; Budnick, Christopher J.; Walters, Kenneth S.; Bind, Marie-Abèle (Psychological Trauma: Theory, Research, Practice, and Policy, 2024)
Keywords: dept.psy; peer-reviewed

Social anxiety and employment interviews: does nonverbal feedback differentially predict cortisol and performance? - Budnick, Christopher J.; Anderson, Eden M.; Santuzzi, Alecia M.; Grippo, Angela J.; Matuszewich, Leslie (Anxiety Stress and Coping, 2019)
Background & Objectives: Interviewers often provide positive nonverbal feedback to reduce interviewees' anxiety. Socially anxious individuals typically harbor negative self-views discrepant with positive feedback. We examined whether nonverbal feedback and social anxiety jointly influence cortisol responses to, and performance during, interviews. Design: An experimental between-subjects design randomly assigned participants to feedback condition. Methods: Undergraduate students (N = 130) provided saliva and completed social anxiety, interview anxiety, and affective measures before a simulated interview. Following a standardized script, a confederate interviewer provided positive, ambiguous, or negative nonverbal feedback. Participants then provided saliva and completed self-focused attention and self-awareness measures. Confederate interviewers and an external rater evaluated participants' anxiety displays, assertive behavior, and performance. Results: Positive feedback decreased cortisol and improved performance for low social anxiety participants. Socially anxious participants exhibited higher cortisol but did not exhibit significant differences in performance after positive compared to negative feedback. Conclusions: Consistent with previous findings, positive feedback did not benefit socially anxious interviewees. Positive feedback increased physiological arousal relative to negative feedback but did not hinder performance among people high in social anxiety. These results provide novel information about the interactive influence of social anxiety and nonverbal interviewer feedback on arousal, self-focus, and interview performance.
Keywords: Anxiety; Arousal; Attention; Feedback; Female; Humans; Hydrocortisone; Interviews as Topic; Job Application; Male; Saliva; Social anxiety; anxiety; arousal; attention; chemistry; controlled study; cortisol; dept.psy; feedback system; female; human; hydrocortisone; interview; interview anxiety; interviews; job finding; male; pathophysiology; peer-reviewed; psychology; randomized controlled trial; saliva; self-verification

Fear of Missing Out’s (FoMO) relationship with moral judgment and behavior - McKee, Paul C.; Senthilnathan, Ithika; Budnick, Christopher J.; Bind, Marie-Abèle; Antonios, Imad; Sinnott-Armstrong, Walter (PLOS ONE, 2024)
Across three online studies, we examined the relationship between the Fear of Missing Out (FoMO) and moral cognition and behavior. Study 1 (N = 283) examined whether FoMO influenced moral awareness, judgments, and recalled and predicted behavior of first-person moral violations in either higher or lower social settings. Study 2 (N = 821) examined these relationships in third-person judgments with varying agent identities in relation to the participant (agent = stranger, friend, or someone disliked). Study 3 (N = 604) examined the influence of recalling activities either engaged in or missed out on these relationships. Using the Rubin Causal Model, we created hypothetical randomized experiments from our real-world randomized experimental data with treatment conditions for lower or higher FoMO (median split), matched for relevant covariates, and compared differences in FoMO groups on moral awareness, judgments, and several other behavioral outcomes. Using a randomization-based approach, we examined these relationships with Fisher Tests and computed 95% Fisherian intervals for constant treatment effects consistent with the matched data and the hypothetical FoMO intervention. All three studies provide evidence that FoMO is robustly related to giving less severe judgments of moral violations. Moreover, those with higher FoMO were found to report a greater likelihood of committing moral violations in the past, knowing people who have committed moral violations in the past, being more likely to commit them in the future, and knowing people who are likely to commit moral violations in the future.
Keywords: Behavior; Interpersonal relationships; Machine learning; Memory recall; Moral philosophy; Personality; Religion; Social media; dept.csc; dept.psy; peer-reviewed

Sleep Health among Children Adopted from Foster Care: The Moderating Effect of Parent–Child Sleep Interactions - Cifre, Anthony B.; Budnick, Christopher J.; Bick, Johanna; McGlinchey, Eleanor L.; Ripple, Carol H.; Wolfson, Amy R.; Alfano, Candice A. (Behavioral Sleep Medicine, 2024)
Keywords: dept.psy; peer-reviewed

Motivation states to move, be physically active and sedentary vary like circadian rhythms and are associated with affect and arousal - Budnick, Christopher J.; Stults-Kolehmainen, Matthew; Dadina, Cyrus; Bartholomew, John B.; Boullosa, Daniel; Ash, Garret I.; Sinha, Rajita; Blacutt, Miguel; Haughton, Adrian; Lu, Tom (Frontiers in Sports and Active Living, 2023)
IntroductionMotivation to be physically active and sedentary is a transient state that varies in response to previous behavior. It is not known: (a) if motivational states vary from morning to evening, (b) if they are related to feeling states (arousal/hedonic tone), and (c) whether they predict current behavior and intentions. The primary purpose of this study was to determine if motivation states vary across the day and in what pattern. Thirty adults from the United States were recruited from Amazon MTurk.MethodsParticipants completed 6 identical online surveys each day for 8 days beginning after waking and every 2–3 h thereafter until bedtime. Participants completed: (a) the CRAVE scale (Right now version) to measure motivation states for Move and Rest, (b) Feeling Scale, (c) Felt Arousal Scale, and (d) surveys about current movement behavior (e.g., currently sitting, standing, laying down) and intentions for exercise and sleep. Of these, 21 participants (mean age 37.7 y; 52.4% female) had complete and valid data.ResultsVisual inspection of data determined that: a) motivation states varied widely across the day, and b) most participants had a single wave cycle each day. Hierarchical linear modelling revealed that there were significant linear and quadratic time trends for both Move and Rest. Move peaked near 1500 h when Rest was at its nadir. Cosinor analysis determined that the functional waveform was circadian for Move for 81% of participants and 62% for Rest. Pleasure/displeasure and arousal independently predicted motivation states (all p's < .001), but arousal had an association twice as large. Eating, exercise and sleep behaviors, especially those over 2 h before assessment, predicted current motivation states. Move-motivation predicted current body position (e.g., laying down, sitting, walking) and intentions for exercise and sleep more consistently than rest, with the strongest prediction of behaviors planned for the next 30 min.DiscussionWhile these data must be replicated with a larger sample, results suggest that motivation states to be active or sedentary have a circadian waveform for most people and influence future behavioral intentions. These novel results highlight the need to rethink the traditional approaches typically utilized to increase physical activity levels.
Keywords: dept.psy; peer-reviewed

Qualitative and quantitative evidence of motivation states for physical activity, exercise and being sedentary from university student focus groups - Stults-Kolehmainen, Matthew A.; Gilson, Todd A.; SantaBarbara, Nicholas; McKee, Paul C.; Sinha, Rajita; Bartholomew, John B.; Boullosa, Daniel; Budnick, Christopher J.; Bueno, Fabio Amador; Haughton, Adrian; Barker, Jessica L.; Ash, Garrett I. (Frontiers in Sports and Active Living, 2023)
Motivation for physical activity and sedentary behaviors (e.g., desires, urges, wants, cravings) varies from moment to moment. According to the WANT model, these motivation states may be affectively-charged (e.g., felt as tension), particularly after periods of maximal exercise or extended rest. The purpose of this study was to examine postulates of the WANT model utilizing a mixed-methods approach. We hypothesized that: (1) qualitative evidence would emerge from interviews to support this model, and (2) motivation states would quantitatively change over the course of an interview period. Seventeen undergraduate students (mean age = 18.6y, 13 women) engaged in focus groups where 12 structured questions were presented. Participants completed the “right now” version of the CRAVE scale before and after interviews. Qualitative data were analyzed with content analysis. A total of 410 unique lower-order themes were classified and grouped into 43 higher order themes (HOTs). From HOTs, six super higher order themes (SHOTs) were designated: (1) wants and aversions, (2) change and stability, (3) autonomy and automaticity, (4) objectives and impulses, (5) restraining and propelling forces, and (6) stress and boredom. Participants stated that they experienced desires to move and rest, including during the interview, but these states changed rapidly and varied both randomly as well as systematically across periods of minutes to months. Some also described a total absence of desire or even aversion to move and rest. Of note, strong urges and cravings for movement, typically from conditions of deprivation (e.g., sudden withdrawal from exercise training) were associated with physical and mental manifestations, such as fidgeting and feeling restless. Urges were often consummated with behavior (e.g., exercise sessions, naps), which commonly resulted in satiation and subsequent drop in desire. Importantly, stress was frequently described as both an inhibitor and instigator of motivation states. CRAVE-Move increased pre-to-post interviews (p < .01). CRAVE-Rest demonstrated a trend to decline (p = .057). Overall, qualitative and quantitative data largely corroborated postulates of the WANT model, demonstrating that people experience wants and cravings to move and rest, and that these states appear to fluctuate significantly, especially in the context of stress, boredom, satiety, and deprivation.
Keywords: dept.psy; peer-reviewed

Urges to Move and Other Motivation States for Physical Activity in Clinical and Healthy Populations: A Scoping Review Protocol - Stults-Kolehmainen, Matthew A.; Blacutt, Miguel; Bartholomew, John B.; Boullosa, Daniel; Janata, Petr; Koo, Brian B.; McKee, Paul C.; Casper, Regina; Budnick, Christopher J.; Gilson, Todd A.; Blakemore, Rebekah L.; Filgueiras, Alberto; et al. (Frontiers in Psychology, 2022)
Motivation for bodily movement, physical activity and exercise varies from moment to moment. These motivation states may be “affectively-charged,” ranging from instances of lower tension (e.g., desires, wants) to higher tension (e.g., cravings and urges). Currently, it is not known how often these states have been investigated in clinical populations (e.g., eating disorders, exercise dependence/addiction, Restless Legs Syndrome, diabetes, obesity) vs. healthy populations (e.g., in studies of motor control; groove in music psychology). The objective of this scoping review protocol is to quantify the literature on motivation states, to determine what topical areas are represented in investigations of clinical and healthy populations, and to discover pertinent details, such as instrumentation, terminology, theories, and conceptual models, correlates and mechanisms of action. Iterative searches of scholarly databases will take place to determine which combination of search terms (e.g., “motivation states” and “physical activity”; “desire to be physically active,” etc.) captures the greatest number of relevant results. Studies will be included if motivation states for movement (e.g., desires, urges) are specifically measured or addressed. Studies will be excluded if referring to motivation as a trait. A charting data form was developed to scan all relevant documents for later data extraction. The primary outcome is simply the extent of the literature on the topic. Results will be stratified by population/condition. This scoping review will unify a diverse literature, which may result in the creation of unique models or paradigms that can be utilized to better understand motivation for bodily movement and exercise.
Keywords: dept.psy; peer-reviewed